Diagnostic criteria for temporomandibular disorders: Diagnostic accuracy for general dentistry procedure without mandatory commands regarding myalgia, arthralgia and headache attributed to temporomandibular disorder. (18th May 2018) - Österlund, C.; Berglund, H.; Åkerman, M.; Nilsson, E.; Petersson, H.; Lam, J.; Alstergren, P.
Summary: The clinical examination in diagnostic criteria for temporomandibular disorders (DC/TMD) is a strict procedure and comprises mandatory commands. However, learning and using these mandatory commands in general practice have proven to be difficult and their use of DC/TMD is minimal. To investigate whether reliability on a diagnostic level for DC/TMD diagnoses differs between examiners using the mandatory commands or not. Six examiners were divided into two groups: one using the mandatory commands in DC/TMD for the clinical examination and one who did not use the mandatory commands. A reliability assessment was performed twice, one occasion for each group of examiners. The assessment was performed according to the guidelines from the International Network for Orofacial Pain and Related Disorders Methodology. Each group of examiners thereby examined 16 subjects (11 TMD patients and 5 healthy individuals) each, and the diagnostic agreement (reliability) as compared to diagnoses derived by a reference standard examiner was calculated with Cohen' s kappa coefficient. The DC/TMD diagnoses myalgia, arthralgia and headache attributed to TMD were included in the reliability assessment. There was no significant difference regarding diagnostic agreement reliability between the examiners using or not using the mandatory DC/TMD commands. This study indicates that not using the mandatory commands in DC/TMD in general practice does not impair the diagnostic reliability regarding the diagnoses myalgia, arthralgia and headache attributed to TMD compared to including the commands.